The association between emotional eating and depressive symptoms: a population-based twin study in Sri Lanka. (2019) - Herle, Moritz P.; Kan, Carol; Jayaweera, Kaushalya; Adikari, Anushka; Siribaddana, Sisira; Zavos, Helena M.S.; Smolkina, Milana; Sumathipala, Athula; Llewellyn, Clare; Ismail, Khalida; Hotopf, Matthew; Treasure, Janet; et al.
Abstract: This study investigated the genetic and environmental contributions to emotional overeating (EOE) and depressive symptoms, and their covariation, in a Sri-Lankan population, using genetic model-fitting analysis. In total, 3957 twins and singletons in the Colombo Twin and Singleton Study-Phase 2 rated their EOE behaviour and depressive symptoms, which were significantly associated (men: r = 0.11, 95% confidence interval (CI) 0.06–0.16, women: r = 0.12, 95% CI 0.07–0.16). Non-shared environmental factors explained the majority of variance in men (EOE e 2 = 87%, 95% CI 78–95%; depressive symptoms e 2 = 72%, 95% CI 61–83%) and women (EOE e 2 = 76%, 95% CI 68–83%; depressive symptoms e 2 = 64%, 95% CI 55–74%). Genetic factors were more important for EOE in women ( h 2 = 21%, 95% CI 4–32%) than men ( h 2 = 9%, 95% CI 0–20%). Shared-environmental factors were more important for depressive symptoms in men ( c 2 = 25%, 95% CI 10–36%) than women ( c 2 = 9%, 95% CI 0–35%). Non-shared environmental factors explained the overlap between depressive symptoms and EOE in women but not in men. Results differed from high-income populations, highlighting the need for behavioural genetic research in global populations.